Start simplifying.

Simplify by adding zeros.

Apply the distributive property.

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> .

Apply the distributive property.

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>8</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>8</mn><mi>y</mi></mstyle></math> to both sides of the inequality.

Add <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn><mi>y</mi></mstyle></math> and <math><mstyle displaystyle="true"><mn>8</mn><mi>y</mi></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>14</mn></mstyle></math> to both sides of the inequality.

Add <math><mstyle displaystyle="true"><mo>-</mo><mn>8</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>14</mn></mstyle></math> .

Divide each term in <math><mstyle displaystyle="true"><mn>6</mn><mi>y</mi><mo>≥</mo><mn>6</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> .

Simplify the left side.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify the right side.

Divide <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> .

Do you know how to Graph -2(7+y)>=-8(y+1)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.